2017
DOI: 10.1007/s00216-017-0314-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of odorants in wood of Calocedrus decurrens (Torr.) Florin by aroma extract dilution analysis and two-dimensional gas chromatography–mass spectrometry/olfactometry

Abstract: General emissions of volatile organic compounds from wood are well investigated, but only limited information is available on the odor-active substances contained therein. To close this gap, we aimed at specifically elucidating the odorous constituents of wood from incense cedar [Calocedrus decurrens (Torr.) Florin]; this material is commonly used for the production of a range of products such as pencils and interior accessories. Targeted odorant analysis requires specialized techniques combining modern odoran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 13 publications
2
20
0
1
Order By: Relevance
“…Thymoquinone as a naturally occurring, pencil-like smelling substance is a new find in pine wood. However, in our recent study 15 on incense cedar wood, thymoquinone was found to have an even higher odour potency, possibly being one of its key odorants. In pine wood the attribute pencil-like was rated only with an intensity of 1.0 during sensory evaluation whereas in incense cedar wood it was the most dominant odour impression 15 .…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Thymoquinone as a naturally occurring, pencil-like smelling substance is a new find in pine wood. However, in our recent study 15 on incense cedar wood, thymoquinone was found to have an even higher odour potency, possibly being one of its key odorants. In pine wood the attribute pencil-like was rated only with an intensity of 1.0 during sensory evaluation whereas in incense cedar wood it was the most dominant odour impression 15 .…”
Section: Discussionmentioning
confidence: 73%
“…However, in our recent study 15 on incense cedar wood, thymoquinone was found to have an even higher odour potency, possibly being one of its key odorants. In pine wood the attribute pencil-like was rated only with an intensity of 1.0 during sensory evaluation whereas in incense cedar wood it was the most dominant odour impression 15 . This reveals that even in those samples where thymoquinone was detected by olfactometry, it did not impact the overall smell of the pine samples as other compounds were present with much more sensory impact, thereby obviously covering the smell impression of this compound.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This method has initially been developed for analysis of food aroma, but diverse studies show that the methodology is also applicable for odor analysis in the non-food sector [90][91][92][93][94][95][96][97][98].…”
Section: Solvent Assisted Flavour Evaporation (Safe)mentioning
confidence: 99%
“…Spinnennetzdiagramm. 3,4) Nachrichten aus der Chemie| 66 | April 2018 | www.gdch.de/nachrichten weiterer Detektor unerlässlich: die menschliche Nase. Daher werden die Peaks nach der Trennung auf der Säule neben dem FID oder MS noch einem Sniffing-Port zugeführt, an dem ein geschulter Proband Geruchsqualität und -intensität der Substanzen bewertet.…”
Section: Abb 3 Geruchsprofil Der Kiefern-und Der Zedernholzprobe Alsunclassified